Explicit microstructure and electrical conductivity of epoxy/carbon nanotube and green silver nanoparticle enhanced hybrid dielectric composites - Aigbodion, Victor S. (Nanocomposites, 2021)
Carbon nanotubes (CNTs) decorated with silver nanoparticles (AgNPs) are promising nanomaterials for improving the dielectric properties of polymer materials for energy storage and micro-capacitor applications. However, the cost of AgNPs limits their wide application. This work describes the synthesis of green silver nanoparticles (GAgNPs) from cashew leaves and their hybridization with CNTs. These new hybrid nanocomposites were developed by adding 0.1, 0.2, 0.3, 0.4 and 0.5% CNTs and 0.5% GAgNPs in an epoxy matrix. Electrical conductivity, dielectric constant, and capacitor raised as CNTs content increased from 0.1 to 0.5% with 0.5% GAgNPs. The high dielectric constant reported in this work was made possible because of the high electron mobility of GAgNPs, which helps to enhance the conductivity of the epoxy. The highest electrical conductivity and dielectric constant were obtained for hybrid nanocomposites based on 0.5% CNTs and 0.5% GAgNPs. It was established that GAgNPs modified CNTs can be used to enhanced the electrical conductivity, dielectric constant and capacitance of epoxy resins for isotropic conductive adhesives, assemblies, and electronic packaging applications
Keywords: cashew leaves; electrical conductivity; dielectric constant; capacitor and microstructure; Nigeria; Power; University of Nigeria Nsukka; ACE_SPED; ACE: Sustainable Power and Energy Development